Food Value of Two Varieties of Ginger (Zingiber officinale) Commonly Consumed in Nigeria. (18th January 2013) - Ajayi, Olubunmi B.; Akomolafe, Seun F.; Akinyemi, Funmilayo T.
Abstract : Ginger ( Zingiber officinale ) is a well-known and widely used herb, which contains several interesting bioactive constituents and possesses health-promoting properties. The proximate, mineral, antinutrient, amino acid, and phytochemical components of two varieties of ginger ( Zingiber officinale ) were investigated. Amino acid composition was determined using standard analytical techniques. The results obtained in percentages in the two varieties of ginger (white and yellow types) were crude fibre (21.90, 8.30), fat (17.11, 9.89), carbohydrate (39.70, 58.21), crude protein (12.05, 11.65), ash (4.95, 7.45) and moisture (3.95, 4.63) contents respectively. Elemental analysis revealed that potassium (0.98 ppm and 1.38 ppm) is the most abundant, while copper (0.01 ppm) is the least. Phytochemical screening indicated that they are both rich in saponins, anthraquinones, phlobatannin and glycosides. Also, the antinutrient constituents of white ginger were lower than yellow ginger, although the levels of the antinutrient constituents in the two varieties are saved for consumption. The essential amino acids in the two varieties were almost the same, with Leu being the most abundant in both. The two ginger varieties were adequate only in Leu, Phe + Try, and valine based on FAO/WHO provisional pattern. Overall, the findings indicate that the two varieties of ginger are good sources of nutrients, mineral elements, amino acid, and phytochemicals which could be exploited as great potentials for drugs and/or nutritional supplements.